2023
DOI: 10.3389/fenvs.2023.1009942
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge mining for the differentiation pattern with respect to the productivity and trophic status of some selected lakes of Western Himalayas

Abstract: The present study deals with an account of the primary productivity and trophic status of Rewalsar, Kuntbhyog, and Prashar lakes of Western Himalayas. Seasonal variations in gross primary productivity (GPP) (g C m–2 day–1), net primary productivity (NPP, respiration (R), and the NPP/R ratio have been studied and compared with hydrobiological factors. Among various factors, temperature, light, nutrients, and chlorophyll a were accountable for high productivity. Nygaard’s trophic state indices were calculated. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…The results of WQI evidently indicated that both rivulets are appropriate to sustain the diverse aquatic ecological diversity on the basis of the standards of WQI (Table 3). Similar observation was reported by Muhammad and Ullah (2022) in Gomal Zam Dam and its tributaries and Kumar et al (2023) for different lakes of Himachal Pradesh. The aim of water policy in India is to effectively manage and utilize water resources to ensure sustainable development, equitable distribution, and improved water security for all citizens (Kamboj et al, 2022a, 2022b).…”
Section: Resultsmentioning
confidence: 99%
“…The results of WQI evidently indicated that both rivulets are appropriate to sustain the diverse aquatic ecological diversity on the basis of the standards of WQI (Table 3). Similar observation was reported by Muhammad and Ullah (2022) in Gomal Zam Dam and its tributaries and Kumar et al (2023) for different lakes of Himachal Pradesh. The aim of water policy in India is to effectively manage and utilize water resources to ensure sustainable development, equitable distribution, and improved water security for all citizens (Kamboj et al, 2022a, 2022b).…”
Section: Resultsmentioning
confidence: 99%
“…Tinggi rendahnya konsentrasi N dan P sangat tergantung pada aktivitas di sekitar perairan danau sebagai sumber masukan diantaranya adalah aktivitas pertanian, limbah organik dan limbah lainnya yang mengandung N dan P, kalium oksida (K2O) serta sirkulasi dan pertukaran massa air dari dasar perairan danau laguna ke permukaaan yang membawa berbagai muatan di dasar perairan yang bersifat toksik, sebagai ancaman terhadap biota yang di budidayakan, kejadian tersebut terjadi pada saat tahun 2015 silam yang mengakibatkan biota yang di budidayakan mengalami kematian massal. Produktivitas dan status trofik juga di pengaruhi oleh siklus hidrobiologi dan parameter lingkungan seperti suhu, cahaya, nutrient dan klorofil a yang berkorelasi positif terhadap status trofik (Kumar, Jindal et al 2023;Torres-Bejarano, García-Gallego et al 2023;Tometin, Chouti et al 2023).…”
Section: Status Trofik Perairan Danau Lagunaunclassified
“…The pollution‐indicating bioindicators can indicate the effect of pollution before it actually starts (Thakur et al, 2013). Populations of plankton are beneficial for knowing the condition of water in an aquatic ecosystem (Kumar et al, 2023). Bioindicators act as early signals of pollution and can be used to assess the health status of a particular body of water.…”
Section: Introductionmentioning
confidence: 99%